ANALISIS PENERAPAN METODE MEMBACA BERULANG (REPEATED READING) TERHADAP PEMAHAMAN SISWA KELAS IIIA SDN 02 BENGKAYANG - Teresia Wini; Siprianus Jewarut (STKIP Subang, 2026)
This study aims to determine the causes of students’ slow reading ability and the implementation of the Repeated Reading method in improving the reading comprehension skills of class IIIA students at SDN 02 Bengkayang. This study used a qualitative approach with a descriptive method, where data were collected through observation, interviews, questionnaires, and documentation. The results showed that the implementation of the Repeated Reading method helped students read more fluently, become more confident, more active in learning, and understand reading texts more easily. In addition, students were also able to remember the content of the story more easily after repeated reading activities. Factors causing students’ slow reading ability included lack of reading practice, differences in students’ abilities, and low self-confidence when reading in front of the class. Therefore, the Repeated Reading method can help improve elementary school students’ reading comprehension skills.